2014
DOI: 10.3390/ijms151119394
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Suppresses Proliferation and Facilitates Apoptosis of OVCAR-3 Ovarian Cancer Cells through Upregulating MicroRNA-200 and Downregulating MMP-2 Expression

Abstract: Abstract:Catalpol is expected to possess diverse pharmacological actions including anti-cancer, anti-inflammatory and hypoglycemic properties. Matrix metalloproteinase-2 (MMP-2) is closely related to the pathogenesis of ovarian cancer. In addition, microRNA-200 (miR-200) can modulate phenotype, proliferation, infiltration and transfer of various tumors. Here, OVCAR-3 cells were employed to investigate whether the effect of catalpol (25, 50 and 100 μg/mL) promoted apoptosis of ovarian cancer cells and to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Recently, the inhibited effect on inflammation and tumor angiogenesis of catalpol in CRC cells was revealed and catalpol was considered as a potential candidate compound for treating CRC (3,10,20). Significant changes in the miRNA expression profiles were observed in cancer cells after catalpol treatment (8)(9)(10)21). Moreover, the present findings indicated that miR-34a played a tumor-suppressive role during progression of human CRC and cholangiocarcinoma (11,12).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Recently, the inhibited effect on inflammation and tumor angiogenesis of catalpol in CRC cells was revealed and catalpol was considered as a potential candidate compound for treating CRC (3,10,20). Significant changes in the miRNA expression profiles were observed in cancer cells after catalpol treatment (8)(9)(10)21). Moreover, the present findings indicated that miR-34a played a tumor-suppressive role during progression of human CRC and cholangiocarcinoma (11,12).…”
Section: Discussionsupporting
confidence: 50%
“…Catalpol is one of the main active ingredients of R. glutinosa (Di Huang) which has been revealed to have antitumor effects on various of human cancers (5,(8)(9)(10). Recently, the inhibited effect on inflammation and tumor angiogenesis of catalpol in CRC cells was revealed and catalpol was considered as a potential candidate compound for treating CRC (3,10,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that microRNA-200 exhibits a regulatory role in the proliferation of gastric cancer MGC-803 cells and that overexpression of microRNA-200 may inhibit the proliferation of gastric cancer MGC-803 cells (24)(25)(26)(27). Gao et al (28) reported that catalpol suppresses proliferation and facilitates apoptosis in OVCAR-3 ovarian cancer cells through activation of microRNA-200 and downregulating matrix metalloproteinase-2 expression. In the The PI3K/Akt signal transduction pathway serves an important role in cell proliferation, in which Akt is a downstream target protein of PI3K, and continuous activation of the pathway is associated with tumor development (29).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are short, endogenous, non-coding RNAs that modulate several physiological and pathophysiologic processes including proliferation, differentiation, and apoptosis-via post-transcriptional regulation of target gene expression [1][2][3]. During the past ten years, most miRs have been proved to contribute to tumor suppression by induction of cell-cycle arrest and apoptosis [4].…”
Section: Introductionmentioning
confidence: 99%